Web-based Knowledge Based System for Selection of Non-traditional Machining Processes - Chandraseelan R, Edison; R, Jehadeesan; M, Raajenthiren (Malaysian Journal of Computer Science, 2008)
This paper presents a web-based knowledge base system developed for identifying the most appropriate nontraditional machining process to suit specific circumstances based on the input parameter requirements such as material type, shape applications, process economy and some of the process capabilities namely, surface finish, corner radii, width of cut, length to diameter ratio, tolerance etc. The selection procedure proposed in this study is based on the idea that certain characteristics of a part restrict the choice of certain non-traditional machining processes for it to have a relatively small number of alternatives. Designers and Engineers who are geographically separated but well connected by the Internet can use this web-based system to realize process selection. Web technology has immense potential to develop a collaborative design and manufacturing environment. It simplifies the sharing of process knowledge and provides intelligent decision-making in a collaborative way through the Internet. This system employs three-tier web architecture for implementing user module to do the selection and expert module to update the knowledge base. The web-based non-traditional machining process selection system can cut down the product cost, enhance the product quality, and decrease the product lead-time considerably. A wide range of industrial parts has been evaluated in order to demonstrate the performance of the proposed selection procedure.